2022
DOI: 10.1093/jac/dkac141
|View full text |Cite
|
Sign up to set email alerts
|

In vivo exposure–response relationship of meropenem against metallo-β-lactamase-harbouring Pseudomonas aeruginosa: an assessment using MICs from conventional and zinc-limited broth

Abstract: Objectives Previous investigations into metallo-β-lactamase (MBL)-harbouring Enterobacterales suggest that susceptibility testing in zinc-limited media may be more appropriate in predicting β-lactam in vivo activity. There are limited data with MBL-harbouring Pseudomonas aeruginosa. Methods Forty-three MBL-harbouring P. aeruginosa isolates (IMP, n = 11; VIM, n = 12; NDM, n = 10; SPM, n = 10) and two P. aeruginosa control isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Moreover, these results suggest that the cultivation methods often fail to align with the actual antibiotic susceptibility in vivo because they do not replicate the nutritional conditions in the host [113]. For example, MDR Gram-negative bacteria, such as E. coli , Pseudomonas aeruginosa , and Klebsiella pneumoniae , show high resistance to carbapenems due to the presence of excess zinc in Mueller-Hinton media as Zinc is a metal cofactor required for carbapenemase activity [142144]. In validation studies, it was found that K. pneumoniae , E. coli , and P. aeruginosa were also highly resistant to carbapenems when grown in Mueller-Hinton broth [142, 143].…”
Section: Bacterial Metabolism the Innate Immune System And Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, these results suggest that the cultivation methods often fail to align with the actual antibiotic susceptibility in vivo because they do not replicate the nutritional conditions in the host [113]. For example, MDR Gram-negative bacteria, such as E. coli , Pseudomonas aeruginosa , and Klebsiella pneumoniae , show high resistance to carbapenems due to the presence of excess zinc in Mueller-Hinton media as Zinc is a metal cofactor required for carbapenemase activity [142144]. In validation studies, it was found that K. pneumoniae , E. coli , and P. aeruginosa were also highly resistant to carbapenems when grown in Mueller-Hinton broth [142, 143].…”
Section: Bacterial Metabolism the Innate Immune System And Antibioticsmentioning
confidence: 99%
“…For example, MDR Gram-negative bacteria, such as E. coli , Pseudomonas aeruginosa , and Klebsiella pneumoniae , show high resistance to carbapenems due to the presence of excess zinc in Mueller-Hinton media as Zinc is a metal cofactor required for carbapenemase activity [142144]. In validation studies, it was found that K. pneumoniae , E. coli , and P. aeruginosa were also highly resistant to carbapenems when grown in Mueller-Hinton broth [142, 143]. However, when the Mueller-Hinton broth was supplemented with a metal chelator, the bacteria had significantly increased carbapenem sensitivity.…”
Section: Bacterial Metabolism the Innate Immune System And Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation